A bio-composite racing sailboat: Materials selection, design, manufacturing and sailing. (15th March 2017) - Castegnaro, S.; Gomiero, C.; Battisti, C.; Poli, M.; Basile, M.; Barucco, P.; Pizzarello, U.; Quaresimin, M.; Lazzaretto, A.
Abstract: Bio-composites represent an interesting solution for replacing fiber-glass in yachts, with the aim of increasing the environmental sustainability of the nautical sector. This replacement is already occurring in several industrial sectors, from building to automotive. However, the nautical field seems reluctant in embracing this innovation; reasons might be found in the lack of technical references describing the bio-composite boat construction methods and the durability of the yacht within time. The production of a 4.6 m flax-epoxy and balsa wood racing sailboat is here described. The final aim of the paper is providing boat designers and manufacturers with the methods to design and construct a bio-composite craft. Tensile tests were performed on several specimens to obtain the mechanical properties of different fiber batches. Resin absorption tests were conducted to select the natural core and surface treatment, to minimize the final weight of the sandwich laminate. Finally, a specific multi-step infusion technique was developed to manufacture the hull and deck, limiting the boat final weight to 65 kg. After four years from the launch, the boat neither shows structural failure nor damage. This is considered a good test and indicates interesting perspectives for the applicability of bio-composites into the nautical recreational field. Abstract : Highlights: The procedure used to design and build a racing boat with bio-composites is presented. The procedure involves tensile tests, as different batches of natural fibers usually present different mechanical properties To avoid an excessive resin up-taking of the sandwich structure, a specific multi-step infusion technique was developed. The boat races since 2012 with no structural failure. The use of bio-composite for future nautical applications is discussed.